2022
DOI: 10.3389/fonc.2022.1020606
|View full text |Cite
|
Sign up to set email alerts
|

The effects of radiation therapy on the macrophage response in cancer

Abstract: The efficacy of radiotherapy, a mainstay of cancer treatment, is strongly influenced by both cellular and non-cellular features of the tumor microenvironment (TME). Tumor-associated macrophages (TAMs) are a heterogeneous population within the TME and their prevalence significantly correlates with patient prognosis in a range of cancers. Macrophages display intrinsic radio-resistance and radiotherapy can influence TAM recruitment and phenotype. However, whether radiotherapy alone can effectively “reprogram” TAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 87 publications
0
12
0
Order By: Relevance
“…Regarding macrophages, Leblond et al [ 57 ] reported that pro-tumoral M2 macrophages are more resistant to RT that M1 macrophages in the context of glioblastoma. Macrophage polarization by irradiation, however, has also been described dependent on the irradiation dose and scheme [ 13 ]. In our model we cannot distinguish between pro- and anti- tumoral neutrophils or M1 and M2 macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding macrophages, Leblond et al [ 57 ] reported that pro-tumoral M2 macrophages are more resistant to RT that M1 macrophages in the context of glioblastoma. Macrophage polarization by irradiation, however, has also been described dependent on the irradiation dose and scheme [ 13 ]. In our model we cannot distinguish between pro- and anti- tumoral neutrophils or M1 and M2 macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…The polarization of macrophages has been shown to be inducible by irradiation. Dependent on the irradiation dose and scheme the cells are either polarized toward M1 or M2 [ 13 , 14 ]. However, the identification of polarized macrophages in situ remains a major challenge [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…After irradiation, the accumulation of MDSCs in the tumor stroma was found to be elevated ( Lehmann et al, 2008 ). Furthermore, radiation altered the expression levels of TAM-produced chemokines, thereby altering the regulation of T-cell infiltration in cancer tissues ( Inoue et al, 2004 ; Beach et al, 2022 ). However, it is warranted to clarify how the TME is involved in the regulation of radiation-induced TAM recruitment and which MDSC and TAM cell populations should be targeted to improve the anti-cancer treatment.…”
Section: Radiotherapy Effects On Cellular Components Of Tmementioning
confidence: 99%
“…However, they can increase tumour cell susceptibility to NK cells and create a favourable environment for “transferred” NK cells, which may benefit NK cell-infusion therapy [ 78 , 79 ]. Moreover, chemotherapy and radiotherapy can change the phenotype of TAMs to be immunostimulatory [ 80 , 81 ], although their effects on NK cell functions are unknown. Moreover, the response of the TME to chemotherapy and radiation could vary in individual cases.…”
Section: Future Research Directionsmentioning
confidence: 99%